DEVELOPMENT STAGES AND CONFLICTS OF PEDAGOGICAL EDUCATION IN TURKESTAN IN 1920-1930 - Mamatkulova Makhfuza Kozimovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  analyzes  the  stages  of  formation  and  development  of pedagogical education from a scientific and historical perspective against the backdrop of  fundamental  changes  in  the  socio-political  and  cultural  life  of  Uzbekistan (Turkestan)  in  the  1920s  and  30s.  The  author  highlights  the  ideologization  of  the education  system  with  the  change  of  state  administration,  campaigns  to  eliminate illiteracy,  the  abolition  of  old-fashioned  schools  and  madrasas,  and  the  issues  of training teaching staff for new Soviet schools. Special attention is also paid to the role of Soviet educational policy in destroying national values in the region and replacing it with a policy of Russification.